2011
DOI: 10.1073/pnas.1107368108
|View full text |Cite
|
Sign up to set email alerts
|

Systemic augmentation of αB-crystallin provides therapeutic benefit twelve hours post-stroke onset via immune modulation

Abstract: Tissue plasminogen activator is the only treatment option for stroke victims; however, it has to be administered within 4.5 h after symptom onset, making its use very limited. This report describes a unique target for effective treatment of stroke, even 12 h after onset, by the administration of αB-crystallin (Cryab), an endogenous immunomodulatory neuroprotectant. In Cryab −/− mice, there was increased lesion size and diminished neurologic func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 46 publications
6
128
1
1
Order By: Relevance
“…The anti-inflammatory property was not due to influencing the adaptive immune response directly, but rather there was binding and resultant modulation of the proinflammatory mediators in plasma (29). These observations are at the basis of the therapeutic effects seen in both autoimmune and ischemic models of disease, including EAE, stroke, myocardial infarction, and retinal ischemia (25)(26)(27)(28).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The anti-inflammatory property was not due to influencing the adaptive immune response directly, but rather there was binding and resultant modulation of the proinflammatory mediators in plasma (29). These observations are at the basis of the therapeutic effects seen in both autoimmune and ischemic models of disease, including EAE, stroke, myocardial infarction, and retinal ischemia (25)(26)(27)(28).…”
mentioning
confidence: 80%
“…This was true in both HspB5 knock-out and wild-type mice. Subsequent studies have demonstrated that HspB5 is effective in reducing the lesion size in a murine model of stroke (26), reducing inflammation and improving heart function in a model of myocardial infarction (27) and increased oligodendroglial survival in the optic nerve in a model of retinal ischemia (28). Further analyses in these animal models concluded that the protein was immunosuppressive.…”
mentioning
confidence: 99%
“…This dose was previously shown to be effective in EAE and stroke (Ousman et al, 2007;Arac et al, 2011). The total amount of endotoxins administrated intravenously per mouse was 0.5 EU/kg body weight/d, lower than the maximum endotoxin levels set by the FDA for injectable drugs (5 EU/kg body weight/h).…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about the role of CRYAB in the CNS. Recent studies have revealed a protective role for CRYAB in a mouse model of multiple sclerosis [experimental autoimmune encephalomyelitis (EAE)], stroke (Arac et al, 2011), and Alexander disease (Ousman et al, 2007;Hagemann et al, 2009). In EAE, CRYAB acts as a negative modulator of inflam-mation and prevents demyelination and disease symptoms (Ousman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that extracellular action of aB-crystallin may contribute to its recently reported anti-inflammatory effects in in vivo model systems. 36,37 On the other hand, the aB-crystallin mini-chaperone is taken up by hfRPE by specific transporters so that the mini-chaperone may act both intracellularly and extracellularly. Nanoparticles containing aB-crystallin minichaperone showed a prominent and uniform uptake by hfRPE cells.…”
Section: Discussionmentioning
confidence: 99%